Modal analysis and dispersion curves of an annular waveguide having a guiding-region cross section bounded by two lemniscates of Bernoulli - Singh V.; Prasad B.; Ojha S.P. (My University, 2025)
The paper presents the modal properties and dispersion curves of a new annular lightguide with a guiding-region cross section bounded by two lemniscates of Bernoulli. We consider a new coordinate system (ξ, η, z) appropriate for the proposed structure. Using this coordinate system and the boundary conditions of the guide under weak guidance approximation, the eigenvalue equation is derived analytically. The dispersion curves for some low-order modes are then obtained.